ANALISIS PEMILIHAN MODA TRANSPORTASI BERDASARKAN PREFERENSI MAHASISWA UNIVERSITAS TARUMANAGARA - Hansel, Deren; Leo, Edison; Angkat, Hokbyan R.S (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2025)
Tarumanagara University is an educational institution surrounded by a lot of public transportation services around it, but has a major problem which is traffic congestion around the campus. This condition makes students look for alternative transportation that is more flexible, such as private vehicles or online transportation become the main choice for most students in dealing with congestion. This study aims to recognize the character of the selection of transportation types as well as understand the factors that have an influence on student preferences regarding the selection of transportation modes to campus. This study was conducted by applying a descriptive analysis approach to the choice of transportation modes by students and cross tabulation analysis for variables that influence the choice of transportation modes by Tarumanagara University students. The results showed that the majority of student respondents chose private vehicles (58.7%) compared to public transportation (41.3%). Then aspects of consideration/reasons such as low cost (59.0%), speed (73.0%) and availability (65.5%) are the main aspects of consideration that are dominantly chosen by student respondents. The conclusion of this study explains that the variables of gender category, pocket money, transportation costs, vehicle ownership, distance traveled, and travel time have a significant and reliable influence on the transportation mode preference variable. Abstrak Universitas Tarumanagara merupakan institusi pendidikan yang dikelilingi banyak sekali layanan transportasi publik di sekitarnya, namun memiliki masalah utama yaitu kemacetan lalu lintas di sekitar kampus. Kondisi ini membuat mahasiswa mencari transportasi alternatif yang lebih fleksibel, seperti kendaraan pribadi atau angkutan online menjadi pilihan utama bagi sebagian besar mahasiswa dalam menghadapi kemacetan. Studi ini bertujuan untuk mengenali karakter pemilihan jenis transportasi sekaligus memahami faktor-faktor yang memiliki pengaruh terhadap preferensi mahasiswa terkait pemilihan moda transportasi menuju kampus. Penelitian ini dilaksanakan dengan cara menerapkan pendekatan analisa deskriptif terhadap pilihan moda transportasi oleh mahasiswa serta analisa tabulasi silang untuk variabel yang memengaruhi pilihan moda transportasi oleh mahasiswa Universitas Tarumanagara. Hasil penelitian menunjukan mayoritas responden mahasiswa memilih kendaraan pribadi (58,7%) dibandingkan dengan kendaraan umum (41,3%). Kemudian aspek pertimbangan/alasan seperti biaya murah (59,0%), kecepatan (73,0%) dan ketersediaan (65,5%) menjadi aspek pertimbangan utama yang dominan dipilih oleh responden mahasiswa. Kesimpulan dari penelitian ini menjelaskan variabel kategori jenis kelamin, uang saku, biaya transportasi, kepemilikan kendaraan, jarak tempuh dan waktu tempuh memiliki pengaruh yang signifikan dan reliabel terhadap variabel preferensi moda transportasi.